2023
DOI: 10.1108/lht-08-2022-0398
|View full text |Cite
|
Sign up to set email alerts
|

Public information needs during the COVID-19 outbreak: a qualitative study in mainland China

Abstract: PurposeThe impact of COVID-19 has led to a surge in the public’s reliance on the Internet for pandemic information, and the policy of home isolation has exacerbated this. This study aimed to investigate public information needs and ways of accessing and disseminating information during COVID-19 in mainland China.Design/methodology/approachThis study used a qualitative research approach to conduct semi-structured interviews with 15 participants from 9 cities in mainland China about information needs and access … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 146 publications
0
10
0
Order By: Relevance
“…, 2022; Yu et al ., 2022b; Sung and Chiu, 2022; Meng et al. , 2023; Yi and Chiu, 2023; Guo et al ., 2021; Nadi-Ravandi and Batooli, 2023). Studies have shown that smartphones have become people's most crucial reading devices (Ezeamuzie et al ., 2022; Adeyemi, 2021; Dong et al ., 2021; Yip et al ., 2021; Zhang et al ., 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2022; Yu et al ., 2022b; Sung and Chiu, 2022; Meng et al. , 2023; Yi and Chiu, 2023; Guo et al ., 2021; Nadi-Ravandi and Batooli, 2023). Studies have shown that smartphones have become people's most crucial reading devices (Ezeamuzie et al ., 2022; Adeyemi, 2021; Dong et al ., 2021; Yip et al ., 2021; Zhang et al ., 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to the mass production of digital resources, people spend much time on electronic devices daily to obtain useful information (Cheung et al, 2022;Yu et al, 2022a;Ding et al, 2021;Wang et al, 2016). Remarkably, after the COVID-19 outbreak, people have used electronic devices to read and interact more frequently due to social distancing requirements (Chan et al, 2022;Yu et al, 2022b;Sung and Chiu, 2022;Meng et al, 2023;Yi and Chiu, 2023;Guo et al, 2021;Nadi-Ravandi and Batooli, 2023). Studies have shown that smartphones have become people's most crucial reading devices (Ezeamuzie et al, 2022;Adeyemi, 2021;Dong et al, 2021;Yip et al, 2021;Zhang et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…More institutions have moved to online learning mode in the past few years due to COVID-19 (Kabigting et al ., 2023; Li et al ., 2023; Tse et al ., 2022; Ye and Ho, 2022; Yi and Chiu, 2023; Yu et al ., 2023) and changed information habits of youths (Ding et al ., 2021b; Dong et al ., 2021; Yu et al ., 2022) and curricula (Ho et al ., 2023; Yew et al ., 2022; Li and Chiu, 2022; Ng et al ., 2022). Thus, a focus is on the dropout rates of massive open online courses (MOOCs).…”
Section: Bibliometric Analytics On Educationmentioning
confidence: 99%
“…People have changed their information habits to digital, particularly for the newer generation (Cheung et al ., 2023; Dai and Chiu, 2023; Guo et al ., 2022; Nguyen and Le, 2021; Leung et al ., 2022; Li et al ., 2021; Lu et al ., 2023; Soroya and Faiola, 2023; Sung and Chiu, 2022; Yi and Chiu, 2023; Yu et al ., 2022; Wong and Chiu, 2023c; Wong et al ., 2023b; Wu and Zhang, 2022). Further, digitalization technology enables libraries and scholars to share links and content on social media to attract users (Banshal et al ., 2022; Lo et al ., 2019; Ocran and Afful-Arthur, 2022; Pianzola et al ., 2022; Yang et al ., 2020; Wu et al ., 2022a; Wu, 2022; Xu and Du, 2022).…”
Section: Advances In Library Information Managementmentioning
confidence: 99%